Conditional neuronal deletion of microRNA ‐141/200c cluster, but not microRNA ‐181a/b‐1 cluster, is protective against experimental stroke in male mice - Xu, Lijun; Griffiths, Brian; Sun, Xiaoyun; Greer, Majesty; Chang, Heather; McMillin, Elijah; Manis, Elizabeth; Russo, Isabella; Dean, Claire Ai Jue; Stary, Creed M. (Physiological reports, 2025)
MicroRNAs (miRs) regulate the translation of target genes often in a cell‐type specific manner. We previously demonstrated that downregulation of either miR‐181a or miR‐200c with intracranial injection of an inhibitor is protective against experimental stroke in mice. Here, we generated genetic lines of inducible Ca 2+ ‐calmodulin kinase IIα (CKIIα) neuronal miR‐181a/b‐1 and miR‐141/200c cluster deletion to investigate whether the protective effect of their inhibition could be neuron‐specific. Jackson Lab strains Mirc14tm1.1Czc/J and Mirc13tm1Mtm/Mmjax were each crossed with the tamoxifen‐inducible Cre‐recombinase strain B6;129S6‐Tg, CKIIα‐cre/ERT2. Adult double transgenic male mice were randomized and treated with 3 mg tamoxifen or vehicle via oral gavage for 7 days prior to 1 h middle cerebral artery occlusion (MCAO) or sham surgery. Mice were assessed for gross motor function at 24 h and then sacrificed for quantification of infarct volume. Separate animals were assessed for cell‐type specific brain expression of miR‐181a and miR‐200c via combined fluorescent immunohistochemistry and in situ hybridization. Brains from tamoxifen treated mice exhibited selective miR deletion in CKIIα neurons. Infarct volumes were significantly lower, and neurological scores significantly improved in CKIIα/miR‐200c mice pretreated with tamoxifen versus vehicle alone. In contrast, no difference was observed in infarct volume or neurological score in CKIIα/miR‐181a mice pretreated with tamoxifen versus vehicle.